Arbuscular Mycorrhiza as an Essential Ecotechnological Tool: A Critical Review of Literature on the Role of AMF in the Sustainability of Cultivation and Conservation of Palms - George Ray, SettingsJoseph; T Nadesan, Sreeja (Algerian Journal of Biosciences, 2024)
Palms are an ecologically and economically significant family of plants, including many crops. Sound knowledge of the ecology of arbuscular mycorrhizal fungal (AMF) association in plants is essential to the sustainable cultivation of crops and the conservation of sensitive species. The current Review is the first-ever comprehensive critical analysis of literature on AMF in the sustainable cultivation and conservation of palms, which reveals the gaps in existing studies and explains the specific needs of future investigations on AMF in Palms. AMF in only 2% of the known palms explored so far; a majority of wild palms and cultivated palms in many different regions remain unexplored. However, currently, a high diversity of 85 species of AMF from about 43 palms are known. The beneficial roles of AMF in palms include boosting productivity, assisting in the in-vitro raising of seedlings, and providing immunity to diseases and environmental stress. However, the identification of external and internal variables crucial to AMF association in palms in the field, long-term monitoring of AMF's beneficial influence in palms, and experimental application of AMF from wild palms in cultivated palms are further required. Overall, AMF dependence, responsiveness, and effectiveness in palms also need thorough investigation in the future.